PENGARUH EKSTRAK MINYAK CUMI PADA UMPAN BUBU LIPAT DASAR TERHADAP HASIL TANGKAPAN DI MUARA GAMPONG JAWA, KOTA BANDA ACEH - MHD Raihan; Elfa Yeni; Chaliluddin (JURNAL KREASI RAKYAT, 2025)
This study explores the potential of squid oil in folding trap bait in an effort to increase catches and standard of living for traditional pond farmers who have a livelihood catching crabs as additional income and need alternative methods of catching crabs that are more effective. This study aims to determine the composition of the results, the effect of folding trap catches with the addition of squid oil extract and identify the types of catches that have economic value. The method used in this study is quantitative descriptive through direct observation and experimental with a quasi-experimental design involving 2 treatments, namely experiment and control and data analysis using the ANOVA test factorial design method with a basic design of RAK for differences in bait concentration. The results of the study stated that the composition of the catch showed variations in terms of both weight and number caught. There is a composition with 5% squid oil extract producing a catch of 13 (1800 grams), 10% squid oil extract as many as 10 (1,350 grams) and 15% squid oil extract as many as 9 (1300 grams). The addition of squid oil extract has been proven to have a positive impact on increasing fishermen's income, previously 2-3 crabs per day and the catch can also increase the economic value for fishermen because the average weight of the catch is 100 grams - 300 grams with distribution to collectors for 40 thousand per kg.